Association of anti-cyclic citrullinated peptide antibody with clinical features in patients with psoriatic arthritis. Issue 2 (3rd March 2020) - Hagiwara, Shinya; Tsuboi, Hiroto; Terasaki, Toshihiko; Terasaki, Mayu; Toko, Hirofumi; Shimizu, Masaru; Honda, Fumika; Yagishita, Mizuki; Ohyama, Ayako; Takahashi, Hiroyuki; Yokosawa, Masahiro; Asashima, Hiromitsu; et al.
Abstract: Background: Although anti-cyclic citrullinated peptide antibody (anti-CCP Ab) is reported to be found in 5–20% of patients with psoriatic arthritis (PsA), its clinical significance has not been elucidated. Objective: To clarify the association of anti-CCP Ab with clinical features in PsA. Methods: Patients were enrolled who fulfilled the classification criteria for psoriatic arthritis (CASPAR) criteria and visited our hospital. We retrospectively compared clinical characteristics between those who were positive and negative for anti-CCP Ab and further compared changes in disease activity in the patients treated with biological disease-modifying anti-rheumatic drugs (DMARDs). Results: We examined 41 patients (11 females), seven were anti-CCP Ab-positive and 34 were negative. Age (55.0 ± 15.1 years old) and frequency of lung involvements (71.4%) in the anti-CCP Ab-positive group were significantly higher than those (40.0 ± 16.0 and 0%, respectively) in the negative group ( p   <  .05). Rheumatoid factor (RF) titer (749.4 ± 860.7 U/mL) and MMP-3 (604.8 ± 1060.6) in the anti-CCP Ab-positive group was significantly higher than that (3.6 ± 4.4 U/mL and 111.2 ± 77.4, respectively) in the negative group ( p   <  .05). Five patients were treated with tumor necrosis factor (TNF) inhibitors (infliximab (IFX): 3 and adalimumab (ADA): 2) in the anti-CCP Ab-positive group, while in the negative group there were 11 (IFX: 6, ADA: 4, and etanercept (ETN): 1). Within 6 months of treatment, arthritis did not improve with TNF inhibitors in the anti-CCP Ab-positive group, whereas it improved significantly in the negative group. Conclusion: In patients with PsA, anti-CCP Ab might be related to lung involvements, elderly onset, RF and MMP-3 titers, and resistance to TNF inhibitor.